A transiting, temperate mini-neptune orbiting the M dwarf TOI-1759 unveiled by TESS - Espinoza, Néstor; Pallé, Enric; Kemmer, Jonas; Stock, Stephan; Molaverdikhani, Karan; Henning, Thomas; Kreidberg, Laura; Kürster, Martin; Schlecker, Martin; Bluhm, Paz; Pavlov, Alexey; Quirrenbach, Andreas; et al. (The astronomical journal, 2022)
We report the discovery and characterization of TOI-1759 b, a temperate (400 K) sub-Neptune-sized exoplanet orbiting the M dwarf TOI-1759 (TIC 408636441). TOI-1759 b was observed by TESS to transit in Sectors 16, 17, and 24, with only one transit observed per sector, creating an ambiguity regarding the orbital period of the planet candidate. Ground-based photometric observations, combined with radial-velocity measurements obtained with the CARMENES spectrograph, confirm an actual period of 18.85019 ± 0.00014 days. A joint analysis of all available photometry and radial velocities reveals a radius of 3.17 ± 0.10 R ⊕ and a mass of 10.8 ± 1.5 M ⊕. Combining this with the stellar properties derived for TOI-1759 (R ⋆ = 0.597 ± 0.015 R ⊙; M ⋆ = 0.606 ± 0.020 M ⊙; T eff = 4065 ± 51 K), we compute a transmission spectroscopic metric (TSM) value of over 80 for the planet, making it a good target for transmission spectroscopy studies. TOI-1759 b is among the top five temperate, small exoplanets (T eq < 500 K, R p < 4 R ⊕) with the highest TSM discovered to date. Two additional signals with periods of 80 days and >200 days seem to be present in our radial velocities. While our data suggest both could arise from stellar activity, the later signal’s source and periodicity are hard to pinpoint given the ∼200 days baseline of our radial-velocity campaign with CARMENES. Longer baseline radial-velocity campaigns should be performed in order to unveil the true nature of this long-period signal.
Gesehen am 25.03.2022